2020
DOI: 10.1093/nar/gkaa317
|View full text |Cite
|
Sign up to set email alerts
|

H2B ubiquitylation enhances H3K4 methylation activities of human KMT2 family complexes

Abstract: In mammalian cells, distinct H3K4 methylation states are created by deposition of methyl groups by multiple complexes of histone lysine methyltransferase 2 (KMT2) family proteins. For comprehensive analyses that directly compare the catalytic properties of all six human KMT2 complexes, we employed a biochemically defined system reconstituted with recombinant KMT2 core complexes (KMT2CoreCs) containing minimal components required for nucleosomal H3K4 methylation activity. We found that each KMT2CoreC generates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…1 ). Only KMT2G does not require uH2B to form H3K4me3 in an in vitro reconstituted chromatin system [ 28 ] (Table 1 ). Our group has previously shown that the ubiquitination of H2B is dependent on transcription [ 29 ].…”
Section: H3k4me3 Writers Erasers and Readersmentioning
confidence: 99%
“…1 ). Only KMT2G does not require uH2B to form H3K4me3 in an in vitro reconstituted chromatin system [ 28 ] (Table 1 ). Our group has previously shown that the ubiquitination of H2B is dependent on transcription [ 29 ].…”
Section: H3k4me3 Writers Erasers and Readersmentioning
confidence: 99%
“…DPY30, regarded as the core unit of the risk signature, is a common essential subunit of all Set1/MLL complexes and facilitates H3K4 methylation in cells [ 28 , 29 ]. The WDR5, RbBP5, ASH2L, and DPY30 are collectively called WRAD, which make Set1/MLL complexes capable of di- and tri-methylation activities [ 30 ], while MLL by itself is a mono-methyltransferase [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their relationship with each other is actually the cross-linking interaction between various histone modifications. Among the four target genes, CBX8 is involved in the ubiquitination of H2AK119 as part of polycomb repressive complex 1 (PRC1) [ 36 ], DPY30 is involved in the methylation of H3K4 as part of SET1/MLL complex [ 28 , 29 ], and PADI1 is involved in the citrullination of H4R3 and H3R2/8/17 [ 61 ]. They are one of the factors that maintain the homeostasis of histone modifications in the body, or near certain tumor-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…MLL3 and MLL4 monomethylate H3K4 located at the enhancer regions involved in cell type-specific gene expression [ 22 , 23 , 24 , 25 ]. Recent studies have revealed that the activity of KMT complexes is stimulated by the monoubiquitylation of histone H2B, and that distinct subunits components may have a role in determining the levels and state of H3K4 methylation [ 26 , 27 , 28 ].…”
Section: Histone Lysine 4 Methyltransferasesmentioning
confidence: 99%